UJI AKTIVITAS SEDIAAN SPRAY HAND SANITIZER KOMBINASI EKSTRAK DAUN SIRIH HIJAU DAN DAUN SERAI SEBAGAI ANTIBAKTERI TERHADAP Staphylococcus aureus - Mutia M Tuasalamony; Cecilia Anna Seumahu; Anneke Pesik (LP4MK STKIP PGRI Lubuklinggau, 2022)
The content of extracts of green betel leaf and lemongrass leaves have antibacterial compounds to inhibit the growth of Staphylococcus aureus. The purpose of this study was to determine the antibacterial activity of the spray hand sanitizer preparation of a combination of green betel leaf extract and lemongrass against Staphylococcus aureus. This type of research is an experimental laboratory. Green betel leaves and lemongrass leaves were partially macerated, formulated to be hand sanitizers in a ratio of 1:2, 2:1, and 2:2. The formula was tested for antibacterial activity by the dilution method. The results showed that the hand sanitizer combination of green betel leaf extract and lemongrass had antibacterial activity against Staphylococcus aureus with a bactericidal formula of 0 CFU/ml and total bacteria with an antiseptic formula of 0 CFU. From this research, it is known that the spray hand sanitizer combination of green betel leaf extract and lemongrass is effective in inhibiting and killing Staphylococcus aureus.